2020
DOI: 10.1055/s-0040-1718397
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Atrial Fibrillation and Adverse In-Hospital Outcome in Patients with Acute Pulmonary Embolism

Abstract: Atrial fibrillation (AF) can be secondary to acute pulmonary embolism (PE). This study aimed to investigate the prognostic impact of new-onset AF on patients with acute PE. In this study, 4,288 consecutive patients who were diagnosed with acute PE were retrospectively screened. In total, 77 patients with acute PE and new-onset AF were analyzed. Another 154 acute PE patients without AF were selected as the age- and sex-matched control group. Adverse in-hospital outcome comprised one of the following conditions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The causes and consequences of AF in PE are still a matter of debate. Our results show that adding the AF variable to ESC mortality risk stratification did not lead to the reclassification of patients to higher-risk groups, which is consistent with the findings in other studies [28]. Interestingly, in women, adding a new-onset paroxysmal AF variable to the ESC mortality risk model did significantly improve its prognostic power for both all-cause and PE-related hospital mortality.…”
Section: Discussionsupporting
confidence: 90%
“…The causes and consequences of AF in PE are still a matter of debate. Our results show that adding the AF variable to ESC mortality risk stratification did not lead to the reclassification of patients to higher-risk groups, which is consistent with the findings in other studies [28]. Interestingly, in women, adding a new-onset paroxysmal AF variable to the ESC mortality risk model did significantly improve its prognostic power for both all-cause and PE-related hospital mortality.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study showed that the inclusion of AF in sPESI could improve the prediction of in-hospital adverse events. 23 In another PE cohort, they found AF group had a high proportion of massive PE and in-hospital mortality. 24 Indeed, the in-hospital mortality of PE combined with AF is 20%-32%, and nearly half of the patients suffer from rightsided intracardiac thrombus.…”
Section: Discussionmentioning
confidence: 96%